Academic Lawyers and Legal Practice in England: Towards a New Relationship? - Martin Partington (Legal Education Review)
The theme of this conference — legal academia — raises for discussion and analysis basic questions about the current state and status of the legal academy. It implies historical questions: how have we arrived at the position we are in today? It implies predictive questions: how are we likely to develop in the years ahead? How should we be developing? It also implies comparative questions: is what we do here similar/dissimilar to what goes on in other common law countries? In the civil war jurisdictions? In the (former?) Eastern Bloc countries? A complete and comprehensive analysis of all these issues would require a substantial research agenda. Despite the potentially vast scope of the enterprise sketched out above, this paper addresses a narrower set of issues that revolve around the questions: what should the status of the legal academic be? What should the relationship be between the legal academic and the legal practitioner?l In what follows there will inevitably be a rather narrow focus on the position in England.2 Nevertheless, the conference agenda does suggest that some consideration of the matters discussed here form at least part of the agenda in Australia and New Zealand as well. It must also be acknowledged that much of the inspiration for developments occurring in England derive from experience and expertise developed in Australia and New Zealand. The Paper falls into two main parts: Part One looks at developments at Higher Education policy in Britain and the responses of law schools to them; Part Two explores the changing relationship between legal academics and legal practitioners in England. Finally some conclusions are drawn.